Epithelium-dependent regulation of airways smooth muscle function. A histamine-nitric oxide pathway - Konstantinos Gourgoulianis; Zoe Iliodromitis; Apostolia Hatziefthimiou; Paschalis-Adam Molyvdas (Mediators of Inflammation)
The airway epithelium is responsible for the production of a number of arachidonic acid and nonprostanoid inhibitory factors. Epithelium synthesises nitric oxide (NO) which may be important in regulating the function of airways smooth muscles. We studied in vitro the effect of histamine (100 nM100 μ M) which increases the NO release on rabbit airway smooth muscles induced by 80 mM KCl in the presence or not of 10-5 Methylene blue (MB) (inactivator of guanylate cyclase) or N(G)-monomethyl L-arginine (L-NMMA), a NOS inhibitor. All experiments were done in tracheal muscle strips from 28 rabbits with epithelium and after epithelium removal. The additional use of histamine (1 μ M) on KCl contraction induced a relaxation of 10% of the initial contraction. The additional use of L-NMMA decreased the relaxation to 5% of initial contraction. MB rather than L-NMMA increased the contraction significantly (p<0.01). Epithelium removal increased the contraction induced by KCl (80 mM) and histamine (1 μ M) by about 30% (p<0.001). NO release especially from epithelium regulates the airways smooth muscle functions. Damage to the epithelium may contribute to an increase in airways sensitivity, observed in asthma.